1986
DOI: 10.1093/jac/17.3.373
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, safety and preliminary clinical experiences using foscarnet in the treatment of cytomegalovirus infections in bone marrow and renal transplant recipients

Abstract: Fifty seven episodes of severe cytomegalovirus (CMV) infection were treated with iv foscarnet in 13 bone marrow and 33 renal graft recipients. The ranges of the daily dose, duration, average steady state level and total dose were 23-268 mg/kg, 2-46 days, 42-400 mg/l and 2-399 g, respectively. Adverse effects, such as decreased haemoglobin, decreased renal function and increased serum calcium, were observed in a few patients only. Increased liver enzymes, hallucinations and tremor were seen in one uraemic patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(48 citation statements)
references
References 0 publications
1
47
0
Order By: Relevance
“…The relationship of renal insufficiency to foscarnet use was considered possible in 4 of these 5 patients and was judged unevaluatable in the other. The frequency and severity ofrenal toxicity in our study was in the range ofthat in other studies ofallogeneic BMT recipients and AIDS patients [24,25,[28][29][30][31][32].…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The relationship of renal insufficiency to foscarnet use was considered possible in 4 of these 5 patients and was judged unevaluatable in the other. The frequency and severity ofrenal toxicity in our study was in the range ofthat in other studies ofallogeneic BMT recipients and AIDS patients [24,25,[28][29][30][31][32].…”
Section: Discussionsupporting
confidence: 63%
“…With one exception [17], earlier studies of foscarnet among BMT recipients used continuous intravenous infusions to administer the drug [13,19,28,29,[36][37][38]. In one of these studies that reported data on pharmacokinetics [29], the steady-state serum levels of foscarnet in 13 allogeneic BMT recipients who received a daily dose of foscarnet similar to the dose in our inpatient regimen were 273 ± 43~mol/ L (mean ± SE).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…31 Patients with CMV infection were treated with ganciclovir or foscarnet. 32 Details about treatment have been published elsewhere. 21,23,33,34 …”
Section: Prophylaxis Against Infectionsmentioning
confidence: 99%
“…Foscarnet (trisodium phosphonoformate hexahydrate; PFA) is a drug which, like DHPG, inhibits viral DNA polymerase activity, leading to reversible suppression of viral replication (7,17). In clinical trials in allograft recipients with CMV disease, PFA treatment was associated with suppression of CMV replication and resolution of fever and thrombocytopenia in renal transplant recipients, but not bone marrow transplant recipients, with CMV interstitial pneumonitis (7,17).…”
mentioning
confidence: 99%